2017
DOI: 10.4314/ecajs.v22i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and factors affecting personal protective equipment usage in St. Mary’s Hospital Lacor in Northern Uganda

Abstract: Background: To protect health workers (HCWs) from risky occupation exposure, CDC developed the universal precautions (Ups) including Personal Protective Equipment (PPEs). However compliance to it by HCWs has remained poor even in high-risk clinical situation . The objective of this study was to identify and describe the factors that influence a HCWs' decision to wear PPEs and the barriers that exist in preventing their use Methods: A cross-sectional survey was carried out in the St. Mary's Hospital Lacor in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 6 publications
6
22
0
Order By: Relevance
“…Similarly, those who had not been trained on PPE utilization were less likely to utilize PPE in line with the previous studies [32,36]. On the other hand, inadequate or lack of training on PPE usage shows low PPE utilization [37]. This might be due to the reason training workers on safety and proper PPE use promotes [34,38].…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, those who had not been trained on PPE utilization were less likely to utilize PPE in line with the previous studies [32,36]. On the other hand, inadequate or lack of training on PPE usage shows low PPE utilization [37]. This might be due to the reason training workers on safety and proper PPE use promotes [34,38].…”
Section: Discussionsupporting
confidence: 84%
“…Another study in Northern Uganda showed that 23.7% of nurses, nursing aides, cleaners, and doctors do not know how to donning and doffing PPE. 13.6% of them do not use PPE even when indicated (Okello et al, 2017). This finding implies that the hospital management should perform routine training for their staff about the proper use of PPE.…”
Section: Factors That May Influence the Compliance In Using Ppementioning
confidence: 98%
“…Inconsistent use of safety devices was attributed to discomfort and this in keeping with similar studies that have cited discomfort as a reason for non-compliance with personal protective equipment. [17][18][19] This inconsistency in the use of safety devices buttresses the fact that effective control of workplace hazards cannot be solely achieved through personal protective equipment. 20 Efforts must be put into administrative and engineering controls that minimize exposure of workers to potential and identified hazards, while supporting with personal protective equipment, continuous safety education, monitoring and supervision.…”
Section: Discussionmentioning
confidence: 99%